Clinical Efficacy of Blood Ultrafiltration Therapy in Patients with Acute Decompensated Chronic Heart Failure Running Title: Blood Ultrafiltration Therapy for Heart Failure - He, Yan-Wei; Wang, Feng-Qin; Zhang, Fen-Fang; Chen, Huan-Zhen (Physiological research, 2023)
In this study, we investigated the clinical effects of blood ultrafiltration therapy in patients with acute decompensated chronic heart failure. We enrolled 78 patients with acute decompensated chronic heart failure who were admitted to a hospital from September 2017 to December 2021, and divided them into two groups based on the digital randomization method. The FQ-16 heart failure ultrafiltration dehydrating device blood ultrafiltration therapy was administered to the observation group (39 patients) for 8-16 hours, while the control group (39 patients) received the stepped drug therapy. Echocardiography was used to assess the changes in cardiac function of the patients in both groups before and after treatment. The changes in urine volume, N-terminal pro-B-type natriuretic peptide (NT-proBNP), plasma renin, and serum creatinine levels were measured before and after the treatment to compare the overall response rate of the patients in both groups. The differences in left ventricular end-systolic dimension and left ventricular end-diastolic dimension and the ejection fraction between the groups before treatment were not statistically significant (P > 0.05), however, the left ventricular end-diastolic dimension in the observation group was significantly lower and the ejection fraction was significantly higher (P < 0.05) compared with that before treatment; the urine volume, N-terminal pro-B-type natriuretic peptide (NT-proBNP), plasma renin, and serum creatinine were significantly improved in both groups after treatment compared with that before treatment. All indexes in the observation group were better than those in the control group (P < 0.05), 74.36%. The overall response rate of the observation group was 94.87%, x2 = 4.843 and the difference between groups was statistically significant (P < 0.05). Blood ultrafiltration therapy for patients with acute decompensated chronic heart failure can improve their cardiac and renal functions, reduce NT-proBNP, reduce volume load, and enhance efficacy while ensuring high safety.
Keywords: tepový objem; Humans; Heart Failure; Stroke Volume; srdeční selhání; funkce levé komory srdeční; renin; kreatinin; natriuretický peptid typu B; výsledek terapie; lidé; Biomarkers; diuretika; Creatinine; ultrafiltrace; Renin; Peptide Fragments; biologické markery; Ultrafiltration; Treatment Outcome; Diuretics; peptidové fragmenty; Natriuretic Peptide, Brain; Ventricular Function, Left